Literature Study: Analysis of Literacy and Numeracy Abilities in High School Physics Learning - Sari, Peprina; Fadieny, Nurul; Safriana, Safriana (Jurnal Pendidikan dan Ilmu Fisika, 2024)
The aim of this research is to see and determine the growth of students' literacy and numeracy skills and abilities in physics material. Literacy and numeracy skills in solving physics learning problems refer to numbers and symbols used to make conceptual predictions in data analysis to draw conclusions. This research uses a literature study method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) technique. Based on the results of the analysis of 3 appropriate journals from a database of 200 journals reviewed, it can be concluded that increasing students' literacy and numeracy skills can improve student learning outcomes in effective physics learning, improve learning outcomes and develop and increase interest in physics and the level of students' literacy and numeracy abilities are at the secondary level, and there is a significant positive relationship between literacy and numeracy abilities and physics learning outcomes based on research findings. Students in the high ability category in numeracy literacy are able to state the meaning, use of numbers and basic mathematical symbols. Students with moderate abilities are less precise in using numbers and basic mathematical symbols, some are not able to obtain information, and not all are able to make decisions.